Influence of Team Work on Employee Performance in Community Health Center of Pancoran Mas Depok West Java in 2019 - Gabe Gusmi Aprilla (Universitas Teuku Umar, 2020)
Nowadays organizations that use teams to compete become a trend. Working with teams is more effective and efficient than working individually because tasks are more quickly collected, distributed and more focused. The team facilitates employee participation in decisions. So the team is an effective means for management to democratize the organization and increase employee motivation. However, working with a team is not always effective because some staff prefer to work individually. The purpose of the study was to determine the effect of teamwork with the effectiveness of employee performance. This research method is a descriptive survey, which is a research design conducted using a questionnaire and direct interviews with interview guidelines. The number of samples was 30 people from a total of 75 employees. The results of the relationship between teamwork and team effectiveness show a strong relationship (r = 0.624) and have a positive pattern which means that the more effective teamwork, the more effective the team. The coefficient value with a determination of 0.389 means, the regression line equation that we can explain 38.9% of variations in team effectiveness or the obtained line equation is good enough to explain the team effectiveness variable. Statistical test results found that there was a significant relationship between teamwork and team effectiveness. The results of the statistical tests show that there is a significant relationship between teamwork and the effectiveness of Community Health Center staff (p = 0,0005). The conclusion of teamwork has a positive and significant effect on work effectiveness for the Pancoran Mas Community Health Center staff can be seen from the positive linear equation. After conducting the research it turned out that teamwork was quite positive and significant effect on the effectiveness of work on the Pancoran Mas Community Health Center staff this can be seen from the coefficient of determination (R2) of 38.9%. This value indicates the variable X, namely teamwork is able to explain the variable Y for work effectiveness by 38.9%. While the remaining 61.1% is caused by other factors not examined by this study.